2010
DOI: 10.1007/s00221-010-2438-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring structural learning in handwriting

Abstract: Structural learning suggests that the human nervous system learns general rules that can be applied when controlling actions involving similar structures (e.g. using a variety of bicycles when learning to ride). These general rules can then facilitate skill acquisition in novel but related situations (e.g. a new bicycle). We tested this concept by investigating whether learned asymmetries in handwriting (greater ease in moving the hand rightwards and downwards within Western-educated populations) are present i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…This technology has been used to present two-dimensional line-drawing stimuli on the screen, which participants either need to trace over or simultaneously copy on another area of the screen. Robust point-set registration methods can then be used to post-process the participants' drawings to generate error scores that provide objective measurements of the participants' ability to accurately trace/ copy the stimuli presented [25,26]. This is exactly the type of technique required to capture meaningful measures of VMM ability.…”
Section: Introductionmentioning
confidence: 99%
“…This technology has been used to present two-dimensional line-drawing stimuli on the screen, which participants either need to trace over or simultaneously copy on another area of the screen. Robust point-set registration methods can then be used to post-process the participants' drawings to generate error scores that provide objective measurements of the participants' ability to accurately trace/ copy the stimuli presented [25,26]. This is exactly the type of technique required to capture meaningful measures of VMM ability.…”
Section: Introductionmentioning
confidence: 99%
“…In conjunction with this set-up, we also used a computerised battery of manual fine motor control tests: the Clinical Kinematic Assessment Tool (C-KAT) to provide detailed kinematic investigations of end point control across a range of subtests including tracking, sequential aiming and tracing tasks (Culmer et al 2009). This software platform has been used experimentally as a tool for investigating motor learning and manual control in a number of previous studies (Johnson et al 2010; Gonzalez et al 2011; Raw et al 2012a, b). We have shown previously that these tools capture large changes in postural control (Flatters et al 2014a; Flatters et al in press) and manual control (Flatters et al 2014b) as a function of age.…”
Section: Introductionmentioning
confidence: 99%
“…This task, however, required participants to complete the boxes from right to left with the left hand, and vice-versa with the right hand. The asymmetries in drawing time for each hand may, therefore, have been purely due to task differences as it has been shown that there are costs involved with moving both the preferred and non-preferred hand in the opposite direction to that used when writing (Johnson, Culmer, Burke, Mon-Williams and Wilkie 2010).…”
Section: Introductionmentioning
confidence: 99%